Wind charge controller for golf car using Peripheral Interface Controller (PIC) / Che Rossli Che Mazlam - Che Mazlam, Che Rossli (2011)
This paper presents wind charge controller for golf car using Peripheral Interface Controller (PIC). The purpose of this work is to describe the implementation of a controller for tracking the point of maximum power transfer based on neural networks, using a microcontroller of the PIC family, on energy system that used wind turbines. The general principal behind the controller is to monitor the voltage of the batteries in this system that either sends power from the turbine into the batteries to recharge them, or dumps the power from the turbine into a secondary load if the batteries fully charged. PIC controller system used to prevent overcharging and destroying the batteries. The program was built by using MPLAB software and PICkit 2 programmer. The wind charge controller will begins charging at 6 Volt and it will be fully charged at 9 Volt.